Les récupérateurs de matériaux à Manizales (Colombie) : enjeux et réponses institutionnelles - Carlos Andres Rodriguez; Emmanuel Raufflet (VertigO)
This article looks at the socio-economic situation of informal recyclers in the Global South, based on an analysis of their situation in the Colombian city of Manizales. We present a description and analysis of the social and economic situation of these recyclers, as well as an analysis of public policies and their effects on this situation. Based on this analysis, five courses of action are identified to promote more inclusive public policies aimed at the situation in Manizales, but also in other contexts in Latin America.